Mennictwo cesarskiego Rzymu - Balbuza, Katarzyna (Studia Europaea Gnesnensia, 2011)
REC. KSIĄŻKI The Roman Imperial Coinage, volume II, Part 1: from AD 69–96. Vespasian to Domitian, by I.A. Carradice and T.V. Buttrey (M. Amandry & A. Burnett eds.). Second fully revised edition, Spink&Son Ltd, London 2007, 404 s., 160 tablic.